2018
DOI: 10.1002/jsfa.9246
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the experimental cultivation of peppers in low‐energy‐demand greenhouses. An interdisciplinary study

Abstract: Covering only a small proportion (ca. 20%) of the greenhouse roof with photovoltaic panels contributes considerably to its energy demands without affecting plant growth and quality. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 43 publications
0
12
0
2
Order By: Relevance
“…are not affected by the shading of solar panels on the greenhouse roof. Moreover, tests with PV panels on the greenhouse roof (20%) in pepper cultivation have been described in [42]. These authors concluded that the quality of the pepper fruit is not affected.…”
Section: -Average Photosynthesis Rate At Plant Levelmentioning
confidence: 99%
“…are not affected by the shading of solar panels on the greenhouse roof. Moreover, tests with PV panels on the greenhouse roof (20%) in pepper cultivation have been described in [42]. These authors concluded that the quality of the pepper fruit is not affected.…”
Section: -Average Photosynthesis Rate At Plant Levelmentioning
confidence: 99%
“…A capsaicina, que é o capsaicinoide majoritário das pimentas C. chinense e C. frutescens, demonstrou ser um potente antioxidante, reduzindo a peroxidação lipídica induzida por ferro (DAIRAM et al, 2008). As oleoresinas analisadas nesse estudo apresentaram valores semelhantes às pimentas da espécie Jalapenho (Capsicum annuum) cultivadas em estufa (424 a 587 µmol TE/g amostra) (KAVGA et al, 2018).…”
Section: Figura 2 Fluorescência Relativa Dos Compostos Analisadosunclassified
“…Observou-se uma relação direta da presença de compostos fenólicos com a atividade antioxidante. Os metabólitos secundários das folhas de T. acutifolius contribuíram de maneira significativa para o potencial dessa atividade, enquanto os compostos fenólicos dos frutos de pimenta apresentaram atividade antioxidante mais baixo, porém de acordo com outros resultados já descritos na literatura e esperados para as pimentas (KAVGA et al, 2018;KONCZAK et al, 2010).…”
Section: Figura 2 Fluorescência Relativa Dos Compostos Analisadosunclassified
“…However. photometric and spectroscopic studies of the pepper fruits’ extracts showed decreases in the glass-PV greenhouse ( Kavga et al., 2019 ). The shading net (35% light reduction) was a beneficial tool in the Mediterranean area during the spring-summer season which allowed the adjustment of the light and temperature conditions in greenhouse for pepper resulting in enhancing the yield and antioxidant content ( Caruso et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%